The Duality of State Cooperation within International and National Criminal Cases - (:unkn) unknown (My University, 2016)
This is the first of a series of articles seeking to elaborate responses to challenges to the rule of law. The authors consider certain of the greatest of these challenges to center around illegitimate control of State organs by groups capable of infringing presumptive rights granted under treaty to States that in a systematic and continuous way resort to abuse of process. This Article,dealing with the equality of arms, is therefore only the first of a series exploring both this problem and the manner in which it may be addressed. Whether this concept is dealt with under the theoretical template of the “Dual State” in Europe, or what we have called “State capture” in Latin America, the challengesfor defense lawyers will only be heightened in coming years.